Analysis of NUDIX enzymes across fungi reveals previously unrecognized diversity - Zofia Pasterny; Drishtee Barua; Eugenio Mancera; Anna Muszewska (BMC Genomics)
Abstract Background The NUDIX superfamily encompasses highly diverse enzymes involved in a plethora of biological functions such as mRNA metabolism, DNA repair, and lipid peroxidation. These hydrolases are found in all domains of life and show surprising versatility in terms of the substrates that they process. The knowledge about the diversity of fungal NUDIX proteins is fragmentary, being largely limited to a small number of characterized enzymes from yeasts. To address this knowledge gap systematically, we performed a detailed analysis of the NUDIX hydrolases across 183 fungal proteomes. Results Members of six of the known NUDIX families were present in fungi being particularly abundant in Glomeromycota. Phylogenetic analysis and sequence clustering grouped fungal NUDIX enzymes in 25 subfamilies, 13 of which did not cluster with previously known enzymes. These 13 newly identified subfamilies all belong to the canonical NUDIX family, and structural comparison revealed a typical NUDIX fold with α-β-α sandwich structure. Molecular docking suggested Ap3A and Ap4A as substrates with the highest binding affinity, but their possible cellular roles remain unclear. We also found evidence of expression of most of the genes that encode these enzymes, suggesting physiological relevance. Conclusions Our analysis offers a comprehensive perspective on the structural and sequence relationships of the NUDIX superfamily across fungi with potential to guide experimental characterization of their biological functions.